ANALISIS PENERIMAAN PAJAK KENDARAAN BERMOTOR DI PROVINSI SULAWESI TENGGARA - Ratnasari, Ratnasari (JPEP (Jurnal Progres Ekonomi Pembangunan), 2016)
This study aims to Â to analze motor vehicles tax income in the province of Southeast Sulawesi and factors that affect it. To achieve the aim, panel data was used by combining cross-sectional data and time-series data. A technique of data analysis used was the fixed effect. Result of the study show that simultatenously the variables of the number of motor vehicles, PDRB per capita, mutation of incoming vehicles, and tax arrears had significant effect on motor vehicles tax income in the province of Southeast Sulawesi, whereas partially inly the variable of tax arrears of motor vehicles that had insignificant effect and other variables statistically had insignificant effect on motor vehicles tax income in the province of Southeast Sulawesi Keywords : Motor Vehicle Tax, Number Of Motor Vehicles, Panel Data